Amphiphilic mannose-6-phosphate glycopolypeptide-based bioactive and responsive self-assembled nanostructures for controlled and targeted lysosomal cargo delivery - Mondal, Basudeb; Pandey, Bhawana; Parekh, Nimisha; Panda, Sidharth; Dutta, Tahiti; Padhy, Abinash; Sen Gupta, Sayam (Biomaterials Science, 2020)
Receptors of carbohydrate mannose-6-phosphate (M6P) are overexpressed in specific cancer cells (such as breast cancer) and are also involved in the trafficking of mannose-6-phosphate labeled proteins exclusively onto lysosomes via cell surface M6P receptor (CI-MPR) mediated endocytosis. Herein, for the first time, mannose-6-phosphate glycopolypeptide ((M6P)GP)-based bioactive and stimuli-responsive nanocarriers are reported. They are selectively taken up via receptor-mediated endocytosis, and trafficked to lysosomes where they are subsequently degraded by pH or enzymes, leading to the release of the cargo inside the lysosomes. Two different amphiphilic M6P block copolymers (M6P)GP(15)-(PPO44)-P-A and (M6P)GP(15)-(PCL25)(2) were synthesized by click reaction of the alkyne end-functionalized (M6P)GP(15) with pH-responsive biocompatible azide end-functionalized acetal PPO and azide end-functionalized branched PCL, respectively. In water, the amphiphilic M6P-glycopolypeptide block copolymers self-assembled into micellar nanostructures, as was evidenced by DLS, TEM, AFM, and fluorescence spectroscopy techniques. These micellar systems were competent to encapsulate the hydrophobic dye rhodamine-B-octadecyl ester, which was used as the model drug. They were stable at physiological pH but were found to disassemble at acidic pH (for (M6P)GP(15)-(PPO44)-P-A) or in the presence of esterase (for (M6P)GP(15)-(PCL25)(2)). These (M6P)GP based micellar nanoparticles can selectively target lysosomes in cancerous cells such as MCF-7 and MDA-MB-231. Finally, we demonstrate the clathrin-mediated endocytic pathway of the native FL-(M6P)GP polymer and RBOE loaded (M6P)GP micellar-nanocarriers, and selective trafficking of MCF-7 and MDA-MB-231 breast cancer cell lysosomes, demonstrating their potential applicability toward receptor-mediated lysosomal cargo delivery.